A Novel Secure S-box Design Methodology Based on FPGA and SHA-256 Hash Algorithm for Block Cipher Algorithms (Jun, 10.1007/s13369-024-09251-8, 2024) - Aydin, Yilmaz; Garipcan, Ali Murat; Ozkaynak, Fatih (Springer Heidelberg, 2024)
[Abstract Not Available]